Tendências de pesquisa em ensino-aprendizagem de inglês como língua estrangeira no Brasil: 2005-2009 - Monteiro, Dirce Charara [UNESP] (My University, 2012)
The aim of this paper is to point the main research tendencies in teaching and learning English as a foreign language in the main postgraduate courses in this area, in Brazil, in the period 2005-2010. The adopted methodology for the data collection included the inventory of theses and dissertations, which are included in the sites of the universities with research lines in Applied Linguistics and were produced in the mentioned period. The most productive categories were the ones related to teacher formation, translation, language and technology and studies about teachers and students’ beliefs.

O objetivo deste artigo é apontar as principais tendências de pesquisa na área de ensino-aprendizagem de inglês como língua estrangeira nos principais centros de pós-graduação nessa área, no Brasil, no período 2005-2010. A metodologia utilizada na coleta de dados para a obtenção desse estado da arte incluiu o levantamento de teses e dissertações defendidas no período mencionado nas principais universidades do país e que constam dos sites dos programas de pós-graduação que possuem áreas ou linhas de pesquisa em Linguística Aplicada. As categorias mais produtivas foram as de formação do professor, tradução, linguagem e tecnologia e estudos sobre crenças.
Research tendencies in teaching and learning English as a foreign language in Brazil
Keywords: Research tendencies; Applied Linguistics; English; Tendências de pesquisa; Linguística Aplicada; Inglês